An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Nanoengineered Ce2CaMoO6 double perovskites derived oxide decorated on 2D P@g-C3N4 nanohybrid for the sensitive electrochemical sensing of antiscald agent diphenylamine in food and environmental matrices - Evangeline Jafneel Nixon; Abishek Jayapaul; Sanjay Ballur Prasanna; Chuan-Ming Tseng; Yu-Chien Lin; Da-Hua Wei; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Impact of PM2.5 exposure on gut microbiota abundance and composition in chronic disease patients - Yi-Hsueh Liu; Po Peng; Wei-Chun Hung; Ping-Hsun Wu; Chun-Chi Lu; Yi-Hsiung Lin; Chih-Da Wu; Chao-Hung Kuo; Szu-Chia Chen (Air Quality, Atmosphere & Health, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ultrasonic-vacuum combined effects on Antarctic krill oil oxidation stability: Potential mechanisms of oxygen reduction and influence on reverse micelle - Xue-Chen Pei; Fa-Wen Yin; Chang-Qiang Leng; Xin-Miao Wang; Qian Wang; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Neutrophil extracellular trap (NET)-targeted nanoparticles alleviate myocardial ischemia–reperfusion injury in mice by inhibiting macrophage–myofibroblast transition - Da Lu; Wei Jiang; Xi Zhang; Jiangshui Liang; Meng Xiong; Changzhi Yan; Anyi Lin; Teng Ma; Feng Zhu; Yongqiang Dong (Chemical Engineering Journal, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Revealing the oxidation mechanism of Antarctic krill oil induced by metal ion: Focusing on the influence of reverse micelles - Xue-Chen Pei; Fa-Wen Yin; Meng-Ling Jin; Xin-Miao Wang; Hui-Lin Liu; Liang Song; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Study on mechanism behind browning of Antarctic krill upon hot air drying and its control - Chao Guo; Xiang-Bo Zeng; Bo Peng; Fa-Wen Yin; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Screening and safety assessment of migrating substances released from biodegradable packaging materials into milk - Chuang-Chuang Zhao; Qin-Bao Lin; Cang-Hao Xie; Yi-Qi Liu; Huai-Ning Zhong; Wei-Yue Gu; David Julian McClements; Da Ma (Food Control, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Da-Wei Li; Jin-Zhou Tan; Zhuo-Fan Li; Lin-Jian Ou (Chemosphere, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Tailoring oxygen vacancies in Co3O4 yolk-shell nanospheres via for boosted peroxymonosulfate activation: Single-electron transfer and high-valent Co-oxo species-dominated non-radical pathways - Ta Cong Khiem; Nguyen Nhat Huy; Eilhann Kwon; Stanisław Wacławek; Afshin Ebrahimi; Wen-Da Oh; Suresh Ghotekar; Yiu Fai Tsang; Wei-Hsin Chen; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Arsenic exposure associated with lung interstitial changes in non-smoking individuals living near a petrochemical complex: A repeated cross-sectional study - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Hung-Hsun Lin; Huang‐Chi Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Pollution, 2023)

Blood lead (Pb) is associated with lung fibrotic changes in non-smokers living in the vicinity of petrochemical complex: a population-based study - Wei-Hoong Yau; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Chih-Wen Wang; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

MOF-templated hollow cobalt sulfide as an enhanced Oxone activator for degradation of UV Absorber: Key role of sulfur Vacancy-Induced highly active CoII sites - Ta Cong Khiem; Xiaoguang Duan; Wei-Jie Liu; Young-Kwon Park; Ha Manh Bui; Wen-Da Oh; Suresh Ghotekar; Yiu Fai Tsang; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2023)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

Effect of dermal phthalate levels on lung function tests in residential area near a petrochemical complex - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Hung Su; Jen-taie Shiea; Wen-Yi Lin; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Feedbacks of Alpine Wetlands on the Tibetan Plateau to the Atmosphere - Da Wei; Hui Zhao; Lin Huang; Yahui Qi; Xiaodan Wang (Wetlands, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Genetic analysis and molecular mapping of QTLs associated with resistance to bacterial blight in a rice mutant, SA0423 - Hsin-Yi Tseng; Da-Gin Lin; Hsiao-Ying Hsieh; Ya-June Tseng; Wen-Bin Tseng; Chun-Wei Chen; Chang-Sheng Wang (Euphytica, 2015)

Experimental research on dynamic movement in strata overlying coal mines using similar material modeling - Kan Wu; Gong-Lin Cheng; Da-Wei Zhou (Arabian Journal of Geosciences, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

Escitalopram Ameliorates Forskolin-Induced Tau Hyperphosphorylation in HEK239/tau441 Cells - Qing-Guo Ren; Yan-Juan Wang; Wei-Gang Gong; Qi-Da Zhou; Lin Xu; Zhi-Jun Zhang (Journal of Molecular Neuroscience, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Mechanism of mining subsidence in coal mining area with thick alluvium soil in China - Da-Wei Zhou; Kan Wu; Gong-Lin Cheng; Liang Li (Arabian Journal of Geosciences, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of catechins on Agrobacterium-mediated genetic transformation of Camellia sinensis - Da-Peng Song; Lin Feng; M. M. Rana; Ming-Jun Gao; Shu Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Protective immunity of E. coli-synthesized NS1 protein of Japanese encephalitis virus - Cheng-Wen Lin; Kuang-Ting Liu; Hong-Da Huang; Wei-June Chen (Biotechnology Letters, 2008)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Phylogenetic Analysis of Canine Parvovirus VP2 Gene in Taiwan - Hsien-Chi Wang; Wei-Da Chen; Shiun-Long Lin; Jacky Peng-Wen Chan; Min-Liang Wong (Virus Genes, 2005)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)